2019
DOI: 10.1007/s41979-019-00015-w
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Observations Indicate the Positive Impacts of Discipline-Based Professional Development

Abstract: We compared 236 geoscience instructors' histories of professional development (PD) participation with classroom observations using the Reformed Teaching Observation Protocol (RTOP) that describe undergraduate classes as Student-Centered (score ≥ 50), Transitional (score 31-49) or Teacher-Centered (score ≤ 30). Instructors who attended PD (n = 111) have higher average RTOP scores (44.5 vs. 34.2) and are more frequently observed teaching Student-Centered classes (33% vs. 13%) than instructors with no PD (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 81 publications
2
35
0
Order By: Relevance
“…These results are supported by the importance of the FIRST IV program in the model of learner-centered teaching practice ( Table 5). Participation in FIRST IV was a significant predictor of RTOP scores, reaffirming the value of teaching professional development in improving scientific teaching practices in the classroom [18,100,101].…”
Section: First IV Program Makes a Differencementioning
confidence: 81%
See 1 more Smart Citation
“…These results are supported by the importance of the FIRST IV program in the model of learner-centered teaching practice ( Table 5). Participation in FIRST IV was a significant predictor of RTOP scores, reaffirming the value of teaching professional development in improving scientific teaching practices in the classroom [18,100,101].…”
Section: First IV Program Makes a Differencementioning
confidence: 81%
“…In higher education, instructors are faced with overlapping professional obligations and teaching support and constraints from their institution, department, and peers [14,15]. While past research has explored some of these influences on teaching practices, few studies have taken a multidimensional approach to exploring the factors that influence teaching of learner-centered courses [16][17][18]. As part of a longitudinal study of the Faculty Institutes for Reforming Science Teaching (FIRST) IV program [19,20], we sought to tease apart the relative factors that drive the implementation of learnercentered teaching practices.…”
Section: Introductionmentioning
confidence: 99%
“…Effective faculty professional development draws upon how faculty learn through peer interactions using structured approaches to foster dialogue such as through faculty learning circles (Beach & Cox, 2009;Cox, 2013;Richlin & Essington, 2004), campus or departmental programs (Beyer, Taylor, & Gillmore, 2013;Owens et al, 2018) or discipline-specific workshops such as the Workshop for Early Career Geoscience Faculty. Classroom observation studies of geoscience teaching substantiate the role that discipline-specific workshops can play in faculty adoption of active learning teaching strategies (Manduca et al, 2017;Viskupic et al, 2019). Viskupic et al (2019) identified facilitation of peer learning where participants "work collectively [and] where discourse is supported by participants' commonalities such as discipline" as a critical feature of professional development to support changes in instruction (p. 4).…”
Section: Situated Learning Theory and Community Of Practicementioning
confidence: 99%
“…Classroom observation studies of geoscience teaching substantiate the role that discipline-specific workshops can play in faculty adoption of active learning teaching strategies (Manduca et al, 2017;Viskupic et al, 2019). Viskupic et al (2019) identified facilitation of peer learning where participants "work collectively [and] where discourse is supported by participants' commonalities such as discipline" as a critical feature of professional development to support changes in instruction (p. 4).…”
Section: Situated Learning Theory and Community Of Practicementioning
confidence: 99%
See 1 more Smart Citation